Investigating the translation strategies for English-Vietnamese non-equivalence at word level in the media text = Giải pháp cho vấn đề bất tương đương dịch thuật Anh - Việt ở cấp độ từ vựng trong văn bản truyền thông - Trịnh, Thị Ngọc Hân (2020)
M.A. Thesis. English Linguistics